2022
DOI: 10.3390/ijms23073938
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl) Phthalate Triggers Proliferation, Migration, Stemness, and Epithelial–Mesenchymal Transition in Human Endometrial and Endometriotic Epithelial Cells via the Transforming Growth Factor-β/Smad Signaling Pathway

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a frequently used plasticizer that may be linked to the development of endometriosis, a common gynecological disorder with a profound impact on quality of life. Despite its prevalence, vital access to treatment has often been hampered by a lack of understanding of its pathogenesis as well as reliable disease models. Recently, epithelial–mesenchymal transition (EMT) has been suggested to have a significant role in endometriosis pathophysiology. In this study, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Specifically, no statistically significant alterations in the viability of the three cell types were observed after in vitro DEHP exposure for 24–72 h. These results contradict those published by Kim et al, who described a significant increase in the viability of human EnSC and Ishikawa cells after 72 or 48 h, respectively, of DEHP exposure at 0.01 and 1 µM [ 17 ], respectively, and recently by Kim et al, who observed increases in the proliferation of Ishikawa, and endometriotic and unaffected endometrial epithelial lines 48 h after 25 μM of DEHP exposure [ 20 ]. However, our results are supported by the observations of Cho et al and Huang et al [ 18 , 19 ], who also did not observe alterations in the viability of endometrial cells after DEHP exposure during 24–72 h. Doses of 0.01, 0.1, and 1 nM and 0.2, 2, 20, and 200 µM were used in the studies of Cho et al and Huang et al, respectively [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Specifically, no statistically significant alterations in the viability of the three cell types were observed after in vitro DEHP exposure for 24–72 h. These results contradict those published by Kim et al, who described a significant increase in the viability of human EnSC and Ishikawa cells after 72 or 48 h, respectively, of DEHP exposure at 0.01 and 1 µM [ 17 ], respectively, and recently by Kim et al, who observed increases in the proliferation of Ishikawa, and endometriotic and unaffected endometrial epithelial lines 48 h after 25 μM of DEHP exposure [ 20 ]. However, our results are supported by the observations of Cho et al and Huang et al [ 18 , 19 ], who also did not observe alterations in the viability of endometrial cells after DEHP exposure during 24–72 h. Doses of 0.01, 0.1, and 1 nM and 0.2, 2, 20, and 200 µM were used in the studies of Cho et al and Huang et al, respectively [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 61%
“…Our observations conflict with previous studies with an experimental design comparable to ours, with acute exposure (24–48 h) to DEHP doses in the picomolar to micromolar range. In these previous studies, the authors essentially observed an increase in the inflammatory response and invasiveness of the exposed cells [ 16 , 17 , 19 , 20 , 21 ], which we intended to replicate in our study. Although we were able to recapitulate the invasiveness increase after acute DEHP exposure, we were not able to induce the inflammatory, angiogenic, morphogenic, epigenetic, and steroid receptor expression alterations described in endometrial cells from women with this pathology.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, TAMs promote tumor cell invasion by mediating the degradation of the extracellular matrix through the involvement of cathepsins and matrix metalloproteinases (MMPs) such as MMP7, MMP2, and MMP9 [ 80 ]. Macrophages are also implicated in driving epithelial-mesenchymal transition (EMT) through factors like transforming growth factor-β (TGF-β) and IL-8 [ 81 ] ( Figure 2 ).…”
Section: Tams and Metastasismentioning
confidence: 99%